Clinical groups of dispensary observation in oncogynecology - D. S. Ogay; S. N. Puzin; Yu. G. Payanidi; O. T. Bogova; E. V. Vorobjeva (ABV-press, 2014)
Тhe article presents terms of dispensary, depending on the groups of patients (groups Ia, Ib; II, IIa; III) at all the times cancer patients sub- ject to dispensary observation, restorative and periodic treatment. This article also presents a classification used in dispensary observation.